An Inverse Relationship Between c-Kit/CD117 and mTOR Confers NK Cell Dysregulation Late After Severe Injury - Bösken, Björn; Hepner-Schefczyk, Monika; Vonderhagen, Sonja; Dudda, Marcel; Flohé, Stefanie B. (Frontiers in Immunology, 2020)
Major trauma-induced tissue injury causes a dysregulation of the immune system. Severe systemic inflammation occurs early after the insult. Later on, an enhanced risk for life-threatening opportunistic infections develops that culminates at the end of the first week after trauma. CD56bright Natural killer (NK) cells play a key role in the defense against infection due to their rapid release of Interferon (IFN) γ in response to Interleukin (IL) 12. NK cells are impaired in IFN-γ synthesis after severe injury due to a disturbed IL-12/IFN-γ axis. Thereby, a circulating factor mediates extrinsic suppression of NK cells. Yet unknown cell-intrinsic mechanisms manifest by day 8 after trauma and render NK cells unresponsive to stimulatory cytokines. In the present study, we investigated the origin of such late NK cell-intrinsic suppression after major trauma. Peripheral blood mononuclear cells (PBMC) were isolated from patients 8 day after severe injury and from healthy control subjects and were stimulated with inactivated Staphylococcus aureus. The expression of diverse cytokine receptors, intracellular signaling molecules, and the secretion of IFN-γ by CD56bright NK cells were examined. After stimulation with S. aureus, NK cells from patients expressed enhanced levels of c-kit/CD117 that inversely correlated with IFN-γ synthesis and IL-12 receptor (IL-12R) β2 expression. Supplementation with IL-15 and inhibition of the transforming growth factor receptor (TGF-βR) I reduced CD117 expression and increased the level of IL-12Rβ2 and IFN-γ. NK cells from patients showed reduced phosphorylation of mammalian target of rapamycin (mTOR). Addition of IL-15 at least partly restored mTOR phosphorylation and increased IL-12Rβ2 expression. The reduced mTOR phosphorylation after severe injury was cell-intrinsic as it was not induced by serum factors. Inhibition of mTOR in purified NK cells from healthy donors by rapamycin decreased the synthesis of IFN-γ. Thus, impaired mTOR phosphorylation in response to a microbial challenge contributes to the cell-intrinsic mechanisms that underlie NK cell dysregulation after trauma. Restoration of the mTOR phosphorylation capacity along with inhibition of the TGF-βRI signaling in NK cells after severe injury might improve the immune defense against opportunistic infections.